Qualificação e capacitação no Plano Nacional de Fortalecimento da Agricultura Familiar (PRONAF): ressignificação do trabalho na agricultura familiar do Baixo Amazonas - Maria do Carmo da Silva Dias (2009)
This thesis intended to analyze the qualification and training of family agriculturists who obtained credit from PRONAF Family Agriculture Fortification Program, in Santarém, Region of the lower Amazonas, in Pará state. The aim of this investigation was identify if the courses offered to family agriculturists that participated on PRONAF from 1995 until 2006, by EMATER and CEFT-BAM ONG, involved changes in these agriculturists life. Concerning methodological approach it was predominantly qualitative. During the documental research the documents analyzed define national public politics of formation, expressed in PLANFOR, PNQ also documents of the training institutions focused. The research informants were the different ones involved with the courses trainers, course participants, STTR, EMATER and CEFT-BAM members. There was an attempt to capture, through semi-structured interviews, principles and values transmitted during the courses, their relation with granted credits and knowledge acquired implications in the lives of those who participated on it. This research revealed that in spite of there is not a direct relation between credits granted from PRONAF and family agriculturists qualification and training in addition to other problems put in evidence during the training process, as undoing of credit politics announced by PRONAF; fragmentation and discontinuity in courses, fragility of their contents; insufficient objective conditions for providing the courses and facilitators precarious work conditions, among others, the inclusion of these agriculturists in the courses was able of stimulating reflections and making knowledge development and assimilation possible, reflecting positively on agriculturists work and lives, beyond the foreseen objectives of these courses. The experience with courses or with space and time reserved to courses, in fact, influenced the agriculturists broadening their horizons, furthermore, making them think their lives and their relations in the world over, individual and collectively; rescue solidarity ideals and hopes; search new paths for a better life.